Erosion and accretion of salt marsh in extremely shallow water stages - Chen, Dezhi; Tang, Jieping; Xing, Fei; Cheng, Jun; Li, Mingliang; Zhang, Yiyi; Shi, Benwei; Shi, Lianqiang; Wang, Ya Ping (Frontiers in Marine Science, 2023)
Salt marshes, which commonly exist on the upper tidal flat, provide a natural barrier against sea level rise and coastal storm. The extremely shallow water stages (water depth< 0.2 m), including the initial stage of flood tides and the last stage of ebb tides, can induce a significant impact on sediment dynamics of saltmarshes and associated tidal flats, despite lasting for only a short time (around 10 min), which has been less studied. In this study, two parallel field sites were established to quantify erosion-accretion processes and morphological changes during extremely shallow water stages in salt marshes within Doulonggang tidal flat along the Jiangsu coast. Our results revealed that obvious accretion occurred during extremely shallow water stages, with a total deposition amount of +33.8 mm in vegetated areas and +20.8 mm in unvegetated areas. In contrast, erosion dominated during deep water stages, with a total erosion amount of -22.3 mm at the vegetated site and -32.7 mm at the unvegetated site. The magnitude of bed-level change during extremely shallow water stages was 7~8 times greater than that during deep water stages, even though the duration of extremely shallow water stages was only about 14~15% of the entire tidal cycle. Furthermore, strong winds significantly impacted deposition during extremely shallow water stages compared to calm weather. During the strong wind period, the average bed level change rate reached +0.15 mm/min and +0.12 mm/min in the vegetated and unvegetated areas, respectively. This is significantly higher than the +0.05 mm/min and +0.01 mm/min during the calm weather period. These results reveal that extremely shallow water stages have substantial impacts on sedimentary processes, which are vital for the maintenance of tidal flat systems.